Estimation of River Utroya Ecological State in Intensive Organic Pollution Area Using Plankton Communities ’ Characteristics (Pskov Region) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The changes in characteristics of phytoplankton and zooplankton communities in the river Utroya stretch with the active organic pollution were discussed. The paper shows the effects of pollution on the structural indicators of the communities (species composition, abundance, and biomass). Saprobical analysis was held. Assessment of ecological state of the river stretch was made.